1984
DOI: 10.1002/ana.410150306
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen in the treatment of trigeminal neuralgia: Double‐blind study and long‐term follow‐up

Abstract: A double-blind crossover study of the effects of baclofen was conducted on 10 patients with typical trigeminal neuralgia. Baclofen significantly decreased the number of painful paroxysms in 7 of the 10 patients. An open trial in another 50 patients with trigeminal neuralgia refractory to or unable to tolerate carbamazepine showed that 37 (74%) were relieved of their attacks by baclofen, either alone (12 patients) or in combination with previously ineffective doses of carbamazepine or phenytoin (25). On long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
13

Year Published

1984
1984
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(109 citation statements)
references
References 24 publications
1
95
0
13
Order By: Relevance
“…Other drugs have each been studied in single trials: baclofen (40 to 80 mg a day) was superior to placebo in reducing the number of painful paroxysms (Class II) 30 ; lamotrigine (400 mg a day) was effective as add-on therapy on a composite index of efficacy (Class II) 31 ; pimozide (4 to 12 mg a day) was more effective than CBZ (Class II) 35 ; and tocainide (12 mg a day) was as effective as CBZ (Class III). 34 Tizanidine was better than placebo in a small study but its effect diminished within 1 to 3 months (Class III).…”
Section: For Patients With Classic Tn Does High-resolution Mri Accurmentioning
confidence: 99%
“…Other drugs have each been studied in single trials: baclofen (40 to 80 mg a day) was superior to placebo in reducing the number of painful paroxysms (Class II) 30 ; lamotrigine (400 mg a day) was effective as add-on therapy on a composite index of efficacy (Class II) 31 ; pimozide (4 to 12 mg a day) was more effective than CBZ (Class II) 35 ; and tocainide (12 mg a day) was as effective as CBZ (Class III). 34 Tizanidine was better than placebo in a small study but its effect diminished within 1 to 3 months (Class III).…”
Section: For Patients With Classic Tn Does High-resolution Mri Accurmentioning
confidence: 99%
“…Baclofen selectively activates GABA-B receptors pre-and postsynaptically, leading to a decrease in excitatory transmission and an increase in inhibition, resulting in marked segmental inhibition. In human studies, open (220) and controlled trials (221) have found baclofen to exhibit an analgesic effect in trigeminal neuralgia. Uncontrolled reports have supported an effect in glossopharyngeal and vagoglossopharyngeal neuralgia, and episodic and allodynic pain in some patients with opthalmic postherpetic neuralgia (220).…”
Section: Physical Dependencementioning
confidence: 99%
“…Amédia do escore de qualidade foi 4 (variando de 3 a 5). Os motivos de exclusão dos demais trabalhos foram: ensaio clínico não aleatório [13][14][15][16][17][18][19][20][21][22][23][24] , provavelmente não aleatório [25][26][27] , dor neuropática não especificada 28,29 , e estudos não disponíveis no Brasil ou sequer selecionados em revisões recentes sobre o assunto [30][31][32][33] . Dos artigos incluídos nesta revisão, seis compararam a carbamazepina ao placebo [34][35][36][37][38][39] (Tabela I), os demais compararam a lamotrigina, a tocainida, o topiramato, o dextrometafano, a pimozida, o cloridrato de proparacaína e a tizanidina ao placebo ou ao tratamento ativo (Tabela II).…”
Section: Resultsunclassified